Reshaping the transformed LF model: generating the glottal source from the waveshape parameter Rd - Gobl, Christer (My University, 2017)
Precise specification of the voice source would facilitate better modelling of expressive nuances in human spoken interaction. This paper focuses on the transformed version of the widely used LF voice source model, and proposes an algorithm which makes it possible to use the wave shape parameter Rd to directly control the LF pulse, for more effective analysis and synthesis of voice modulations. The Rd parameter, capturing much of the natural covariation between glottal parameters, is central to the transformed LF model. It is used to predict the standard R-parameters, which in turn are used to synthesise the LF waveform. However, the LF pulse that results from these predictions may have an Rd value noticeably different from the specified Rd, yielding undesirable artefacts, particularly when the model is used for detailed analysis and syn-thesis of non-modal voice. A further limitation is that only a subset of possible Rd values can be used, to avoid conflicting LF parameter settings. To eliminate these problems, a new iterative algorithm was developed based on the Newton-Raphson method for two variables, but modified to include constraints. This ensures that the correct Rd is always obtained and that the algorithm converges for effectively all permissible Rd values.
INTERSPEECH 2017
Keywords: Transformed LF model; Rd parameter; Glottal voice source; Newton-Raphson method; Digital Humanities